Big floods in Doboj and Olovo – an example from May 1965 - Katz, Vera; Ramić, Aida (Historical Thought, 2025)
In this paper, in a form of case study, we described the great flood in May 1965 on the example of Doboj and Olovo, as only a part of the heavy floods that in that year afflicted eastern, central and northern parts of Bosnia and Herzegovina, central Serbia and Vojvodina. According to chronological principle of presentation of events, dramatic moments of the rush of the water elemental were presented, then rescuing people and property, examples of solidarity with the affected population, identification of material damage and result in social and economic development of the affected areas, as well as providing assistance in dealing with the consequences and finding solutions for the defense and protection of the great flood.